Genetically Predicted Circulating Omega-3 Fatty Acids Levels Are Causally Associated With Increased Risk for Systemic Lupus Erythematosus - Wang, Peng; Xiang, Kun; Xu, Yuan-Yuan; He, Yi-Sheng; Hu, Yu-Qian; Ni, Jing; Pan, Hai-Feng (Frontiers in Nutrition, 2022)
Background Accumulating evidence has demonstrated the associations of omega-3 or omega-6 polyunsaturated fatty acids (PUFAs) with the disease activity and inflammatory mediators of systemic lupus erythematosus (SLE), but the evidence of causal links of omega-3 or omega-6 PUFAs on the risk for SLE remains inconclusive. Objectives This study was conducted to evaluate the causal relationships between omega-3/omega-6 PUFAs and SLE by performing the Mendelian randomization (MR) analysis. Methods Genome-wide significant single-nucleotide polymorphisms (SNPs) were obtained from genome-wide association studies (GWASs) of circulating omega-3/omega-6 levels (n = up to 13,544) and GWAS meta-analyses of SLE (n = 14,267), respectively. The bidirectional two-sample MR (TSMR) analysis was conducted to infer the causality. Results The inverse-variance weighted (IVW) method revealed that genetically determined per SD increase in omega-3 levels were causally associated with an increased risk for SLE (odds ratios [ORs] = 1.49, 95% CI: 1.07, 2.08, p = 0.021), but no causal effect of omega-6 on the risk SLE was observed (IVW OR = 1.06, 95% CI: 0.72, 1.57, p = 0.759). In addition, there were no significantly causal associations in genetic predisposition to SLE with the changes of omega-3 and omega-6 levels, respectively (IVW beta for omega-3: 0.007, 95% CI: −0.006, 0.022, p = 0.299; IVW beta for omega-6: −0.008, 95% CI: −0.023, 0.006, p = 0.255). Conclusion The present study revealed the possible causal role of omega-3 on increasing the risk for SLE, it could be the potential implications for dietary recommendations.